FRI0364 PREVALENCE OF THE METABOLIC SYNDROME IN PSORIATIC ARTHRITIS: SYSTEMATIC LITERATURE REVIEW AND RESULTS OF THE CARMA COHORT. (2nd June 2020) - Urruticoechea-Arana, A.; Castañeda, S.; Loza, E.; Oton, T.; Benavent, D.; Martin-Martinez, M. A.; González-Gay, M. A.
Abstract : Background: The cardiovascular burden in psroriatic arthritis (PsA) is well recognized 1 . Objectives: To analyze the prevalence of metabolic syndrome (MetS) in patients with PsA. Methods: We conducted a systematic literature review (SLR) and a sub-analysis of the CARMA cohort. In the SLR, we searched in Pubmed, Embase, the Cochrane Central Library, and the ClinicalTrial until March 2019 using Mesh terms and free text words. We included SLR, clinical trials and observational studies analyzing the prevalence or frequency of MetS in PsA. Two reviewers selected articles, assessed the quality of the studies and collected data independently. The CARMA cohort was designed to establish the cardiovascular (CV) morbidity and associated risk factors for CV disease. It includes data from patients with chronic inflammatory rheumatic diseases (including PsA) of 67 Spanish hospitals. A sub-analysis of the prevalence of metS in PsA was performed using the National Cholesterol Education Program Adult Treatment Panel III criteria updated in 2005, which requires the presence of ≥3 of the following: high waist circumference, low HDL cholesterol level, high triglyceride level, high blood pressure and high fasting glucose values. Results: A total of 18 articles of moderate to high quality, were selected in the SLR. The included patients presented a balanced distribution by sex, with an average age ranging from 42 to 59 years. The frequency of MetS varied from 23.5% to 62.9% depending on the definition of MetS. The most widely used classification method was the National Cholesterol Education Program, followed by the method recommended by the International Diabetes Federation in 2009. A total of 724 patients with PsA were included in the CARMA study, of whom 327 (45.4%) were women and 157 (21.8%) smokers. The mean age at baseline was 51 ± 12 years and the mean duration of PsA disease 9 (4-16) years. Hypertension was the most frequently altered parameter (66.8%), followed by fasting glucose (42.6%) and hypertriglyceridemia (30.6%). Table 1 shows the frequency of patients according to the number of MetS components. A total of 222 (30.6%) PsA patients presented metabolic syndrome. Conclusion: The frequency of the individual components of the MetS is variable according to the method of classification, which makes it difficult to compare between studies. In the CARMA study, the prevalence of MetS was around 30%, which supports the control of individual factors to prevent CV disease. References: [1]Liew JW, et al. Best Pract Res Clin Rheumatol. 2018;32(3):369-389. Disclosure of Interests: ANA URRUTICOECHEA-ARANA: None declared, Santos Castañeda: None declared, Estíbaliz Loza Grant/research support from: Roche, Pfizer, Abbvie, MSD, Novartis, Gebro, Adacap, Astellas, BMS, Lylly, Sanofi, Eisai, Leo, Sobi, Teresa Oton Consultant of: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution), Diego Benavent: None declared, Maria Auxiliadora Martin-Martinez: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD